2017
DOI: 10.1051/matecconf/20179517002
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Thermal Environment and Indoor Comfort of Half Glass Curtain Buildings – a Case of Kouhu Visitor Center in Yunlin County, Taiwan

Abstract: Abstract. Located in the subtropics, the high temperature in summer affects indoor living environments in Taiwan. The use of perspective glass material for modern public buildings increases the transparency of landscape views; however, the solar radiation heat also increases the heat in indoor environment. In particular, visitor centers which offer service functions for large quantities of visitors should satisfy the demands for indoor environment comfort and energy saving. "Numerical simulation" and "field da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The analysis after validation with experimentally collected data allowed to assess that recommendations of the thermal regulations in Chile are more effective in the colder thermal zones 6 and 7. Furthermore, in Ref , the comparison of the impact of different building envelope materials characterized by distinct thermal resistance and thermal conductivity coefficients, as well as sunshine direction and duration, on the heat transmitting indoors thus the indoor temperature and comfort of the indoor environment is carried out using the same coupled numerical and experimental approach. Therefore, the mutual comparison between simulation output and measurements coupled with the analyses of duration of sunshine, temperature distribution, heat balance, and space comfort showed that different building envelope materials as well as sunshine direction and duration are able to considerably affect the heat transmitted indoors by modifying the indoor temperature and affecting the indoor comfort levels.…”
Section: Interaction Of Building Simulation With Other Thermal‐energymentioning
confidence: 99%
“…The analysis after validation with experimentally collected data allowed to assess that recommendations of the thermal regulations in Chile are more effective in the colder thermal zones 6 and 7. Furthermore, in Ref , the comparison of the impact of different building envelope materials characterized by distinct thermal resistance and thermal conductivity coefficients, as well as sunshine direction and duration, on the heat transmitting indoors thus the indoor temperature and comfort of the indoor environment is carried out using the same coupled numerical and experimental approach. Therefore, the mutual comparison between simulation output and measurements coupled with the analyses of duration of sunshine, temperature distribution, heat balance, and space comfort showed that different building envelope materials as well as sunshine direction and duration are able to considerably affect the heat transmitted indoors by modifying the indoor temperature and affecting the indoor comfort levels.…”
Section: Interaction Of Building Simulation With Other Thermal‐energymentioning
confidence: 99%